The Encyclopedia of warships : from World War II to the present day - Jackson, Robert, 1941- (San Diego, CA : Thunder Bay Press, 2006)
An exhaustive reference which features more than 300 military vessels from World War II to the present day; contains numerous action photographs and detailed illustrations showing every aspect of the featured ships. Includes an extensive service history of each ship and specification panels that provide information of displacement, dimensions, armament, speed, and complement.
Introduction -- World War II: Battleships -- Aircraft carriers -- Submarines -- Midget submarines -- Cruisers -- Destroyers -- Assault ships -- Escorts -- The Cold War: Early Cold War aircraft carriers -- Late Cold War aircraft carriers -- Diesel submarines -- Cruisers -- Frigates -- Destroyers -- Assault ships -- The modern era: Modern aircraft carriers -- Ballistic missile submarines -- Nuclear attack submarines -- Diesel attack submarines -- Frigates -- Destroyers -- Assault ships.
Keywords: Warships -- History -- 20th century -- Encyclopedias